Seeds of Self-Determination: How Snuneymuxw Built Economic Power - Moynan, Greg; Brooks, Tasha (Journal of Aboriginal Economic Development, 2025)
This case study examines the development of the Petroglyph Development Group (PDG), the economic organization of the Snuneymuxw First Nation (SFN), tracing its growth from initial community-based ventures to larger undertakings such as the co-management of Saysutshun (Newcastle Island Marine Park) and the acquisition of Casino Nanaimo and Elements Casino Victoria. These initiatives illustrate how gradual capacity-building and learning processes allowed the Nation to engage in complex economic activities over time. This case study highlights four central practices found in the Snuneymuxw experience: starting with manageable projects that build operational knowledge and human capital; maintaining a long-term vision for development; aligning investments with cultural values and place-based priorities; and diversifying revenue sources to strengthen economic resilience. The PDG’s trajectory highlights how community-led planning and culturally grounded decision-making can shape sustainable pathways toward self-determination and economic sovereignty.